Аcute posterior vitreous detachment - P.L. Volodin; S.I. Belyanina (РМЖ "Клиническая офтальмология", 2022)
P.L. Volodin, S.I. Belyanina S. Fyodorov Eye Microsurgery Federal State Institution, Moscow, Russian Federation The detachment of the posterior hyaloid membrane (posterior vitreous detachment /PVD/) means the separation of the posterior vitreous cortex from the internal limiting membrane of the retina and the optic disc. Traditionally, PVD is considered as a physiological process associated with the involutional changes of the vitreous body. In most cases, the early stages of acute PVD are asymptomatic. Patients do not seek for medical care until an acute condition occurs along with the development of typical symptoms. It happens when the posterior hyaloid membrane completely separates from the retina and the optic disc, or when complications of this process develop, such as hemorrhages in the vitreous and retina, retinal breaks/tears and detachment, and macular lesions. Taking into consideration the spontaneous PVD onset and the risk of various complications, it is necessary to conduct a thorough research of the etiology and pathogenesis of this process, identify potential pre disposing and triggering factors, and to define tactics of patient management, timely detection and treatment of complications. It is important to assess the informational value of special instrumental methods of patient examination, such as B-scan ultrasound imaging and optical coherence tomography. These methods open new perspectives for verifying the diagnostic accuracy, revealing complications, visualizing residual vitreoretinal adhesions, and offering tactics for further patient management. Keywords: acute posterior vitreous detachment, posterior hyaloid membrane, peripheral retinal breaks/tears, rhegmatogenous retinal detachment, vitreomacular traction syndrome, B-scan ultrasonography, optical coherence tomography. For citation: Volodin P.L., Belyanina S.I. Аcute posterior vitreous detachment. Russian Journal of Clinical Ophthalmology. 2022;22(4):247–253 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-247-253.